COMORBIDITY OF DEPRESSION AND ANXIETY AMONG STUDENTS AT THE KENYA MEDICAL TRAINING COLLEGES IN KENYA - Menecha, Jared; Muriungi, Susan (Advances in Social Sciences Research Journal, 2020)
Objectives: To determine comorbidity of depression and anxiety among students at the Kenya Medical Training College, Kenya Methodology: This was a cross-sectional descriptive study design. Study participants were basic diploma students in a middle level college in Kenya. Data was collected using a researcher designed self-administered questionnaire for socio-demographic characteristics, the Beck Depression Inventory (BDI) for severity of depression and the Beck Anxiety Inventory (BAI) for the severity of anxiety in all the students in the seven largest KMTC campuses. All the participants gave informed consent. Results: 18.4% and 20.2% of group A and B respectively had moderate depression while 48.5% and 45.8% respectively had severe depression. The equivalents for anxiety in groups A and B were 24.4% and 23.6% for moderate anxiety and 32.1% and 31.5% for severe anxiety. There was a higher rate of depression and anxiety in the second year; with a statistically significant association between depression and anxiety and the year of study in the two groups (p<0.0001 each respectively). All the other social demographic characteristics had no statistically significant association with depression or anxiety in the two groups. There was a higher prevalence of depression and anxiety co-morbidity in both groups which was statistically significant (p<0.0001). Conclusion: Depression and anxiety were highly prevalent and significantly co-existent among the KMTC students. These mental conditions seemed to vary with the level of study training among college students. Therefore, the psychological well-being of college students need to be carefully addressed. There is need to closely monitor anxiety and depression to eliminate the risk factors and consequently prevent the development of adverse outcomes.